Mineralogy and Related Properties of Acid Sulphate Soil from Melaka, Peninsular Malaysia - Jusop, Shamsuddin; Raja Senik, Tuan Omar (1978)
Mineralogical, chemical and physical properties of acid sulphate soil from Kuala Linggi, Melaka, were studied. The study shows that the soil contains kaolinite, montmorillonite, illite, chlorite and pyrite. There are no mineralogical differences between the top and the lower horizons. Both total sulphate and water-soluble sulphate increase with depth. The CEC of the soil is above 16mef1DOg soil, probably due to the presence of montmorillonite. However, the presence of pyrite, which is easily oxidizable to acid sulphate on exposure, makes the soilless suitable for agricultural purposes.